Systematic Literature Review Metode Ilmiah - Isurmin, Isurmin (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines various learning methods and scientific approaches in education, and their impact on improving student and college student competencies. The various studies discussed in this article include variations in the use of learning media, the application of experimental methods, and the application of scientific methods in higher education. The results of the study indicate that the selection of appropriate methods and media plays a major role in increasing student interest and understanding, as well as helping them improve scientific writing skills and scientific attitudes. In addition, the application of systematic and structured methods such as in quantitative and qualitative approaches has a positive impact on the quality of learning and scientific research. This study is expected to provide insight into the importance of innovation in education, both through learning technology and scientific approaches based on valid and reliable research.